Environmental migration and labor markets in Nepal - Maystadt, Jean-François; Mueller, Valerie; Sebastian, Ashwini (International Food Policy Research Institute, 2014)
While an emerging literature cites weather shocks as major determinants of migration, scant evidence exists on how such migration impacts the labor markets of receiving communities in developing countries. We address this knowledge gap by investigating the impact of weather-driven internal migration on labor markets in a post-conflict country, Nepal, using household survey data in 2003 and 2010.